Twitter social network and its interaction between the educational community and higher education institutions in Ecuador - Fernando Mendoza Rodríguez, José (Seven Editora, 2023)
This research work presents an analysis on the interaction of the educational community to the publications made by the institutions of Higher Education in the social network Twitter, five public universities in the country were analyzed, from which 106 data were collected for both retweets and likes in the social network in the years 2017, 2018 and 2019, where a summary of descriptive statistics was established and the average percentage growth rate (TCPP) was determined. The research design was established as non-experimental, field and with a longitudinal descriptive level, where it was obtained as a result that the Escuela Superior Politécnica del Litoral predominates the interaction with its community through a TCPP of 71, 76% and 116.63% for retweets and likes respectively. DOI: 10.56238/pacfdnsv1-035